The political negotiation of the Free Trade Agreement between the United States and the Andean countries - Camacho, Cristina (2016)
This article presents some elements that help highlight the fact that the US-Andean Free Trade Agreement negotiations go beyond trade issues and encompass political issues. In order to do so, the author reviews how the negotiations have been actually carried out. It is shown that there is a ''political negotiation" which involves actors such as businessmen, NGOs, worker unions, among others.